Parents matter : supporting your child with math in grades K-8 - Mistretta, Regina M., 1965- (Rowman & Littlefield, 2016)
This book serves as that guidebook, and its author invites parents to use it while making sense of math with children. Parents and children are encouraged to share and celebrate multiple ways of solving math examples, rather than debate over the better approach.